QUALITIES OF WILL*. Issue 1 (12th February 2014) - Shoemaker, David
Abstract: One of P. F. Strawson's suggestions in "Freedom and Resentment" was that there might be an elegant theory of moral responsibility that accounted for all of our responsibility responses (our "reactive attitudes, " in his words) in a way that also explained why we get off the hook from those responses. Such a theory would appeal exclusively to quality of will : when we react with any of a variety of responsibility responses to someone, we are responding to the quality of her will with respect to us, and when we let her off the hook (either for her action or with respect to her qua agent), we are doing so in virtue of her lacking the capacity for the relevant quality of will. Strawson's own attempt to put forward such a view fails, for reasons Gary Watson has given, but several other theorists have advanced their own, more developed, Pure Quality of Will theories in recent years (including Scanlon, Arpaly, and McKenna). Specifically, there have been three distinct interpretations of "will" defended in the literature, yielding three different possible targets of our responsibility responses: quality of character, quality of judgment, or quality of regard . My first task in this essay will be to show that none of these theories individually can capture all of our responsibility responses, given our deeply ambivalent responses to several marginal cases (e.g., psychopathy, clinical depression, Alzheimer's dementia). One reaction to this fact might be to abandon the quality of will approach altogether. Another, more plausible, reaction is to develop a pluralistic account of responsibility, one that admits three noncompeting conceptions of responsibility, each of which emphasizes one of the three different qualities of will as the target of a distinct subset of our responsibility responses. On this pluralistic approach, marginal agents might be responsible on some conceptions, but not responsible on others. In the bulk of the paper, I discuss each of the relevant subsets of responsibility responses, the different qualities of will they target, what the capacities for the three qualities of will are, and how the pluralistic qualities of will approach could account for our ambivalence in the marginal cases.